A comparison of body composition, speed, flexibility, and balance in fencers - Kosova, S.; Koca Kosova, M.; Manci, E.; Özdalyan, F.; Gümüs, H.; Gencoglu, C. (The online Journal of Recreation and Sport, 2020)
Fencing is a quite popular combatitive sport and applied in 3 different branches. In order to be successful in fencing, it is important to have advanced technical and tactical skills as well as many physical performance parameters. The aim of this study was determine and compare the body composition, speed, balance and flexibility of foil and sabre fencers. 24 foil and 29 sabre fencers included in the study. After body composition measurements, 30 m speed test, sit and reach test, and Y balance test were applied to all participants. There were no statistically differences between body compositions, 30 m speed test and balance test scores of the two groups. Howewer, sit and reach test scores were better in foil fencers compared to sabre fencers (p<.001). Foil plays at a lower tempo than sabre therefore fencers generally have longer lunge in foil. The specific trainings of foil especially for lunge may caused better flexibility levels for the foil fencers. Consequently, these parameters need to be developed in order to increase the competition performance in both branches of fencing.